2020
DOI: 10.35848/1347-4065/aba50c
|View full text |Cite
|
Sign up to set email alerts
|

(Li,Na,K)NbO3-based multilayer piezoceramic with Ag/Pd inner electrodes

Abstract: Lead-free (Li,Na,K)NbO3-based multilayer piezoceramics with Ag/Pd inner electrodes were fabricated. Each multilayer piezoceramic comprised 20 layers, and each layer had a thickness of 13 μm. These multilayer piezoceramics succeeded in driving a high electric field of 16 kV mm−1, while producing a strain of 0.24%. The microstructure was investigated using scanning electron microscopy and scanning transmission electron microscopy. It was found that the grain size was 400 nm and the ceramic layer had high densifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…10,[13][14][15][16][17][18][19][20][21][22] To establish an MBP similar to the PZT system, various lead-free solid solution systems have been investigated and composition-driven variations of crystal structure and properties have been studied. Since the discovery of (K, Na)NbO 3 -based ceramics with properties comparable to PZT, 23) (K, Na)NbO 3 [24][25][26][27][28][29][30] and its related Nb-based materials [31][32][33][34][35][36] have intensively studied with the aim of developing lead-free piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15][16][17][18][19][20][21][22] To establish an MBP similar to the PZT system, various lead-free solid solution systems have been investigated and composition-driven variations of crystal structure and properties have been studied. Since the discovery of (K, Na)NbO 3 -based ceramics with properties comparable to PZT, 23) (K, Na)NbO 3 [24][25][26][27][28][29][30] and its related Nb-based materials [31][32][33][34][35][36] have intensively studied with the aim of developing lead-free piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] This is difficult to achieve with lead oxidebased compounds. The progress of miniaturization and lowering of the operation voltage of piezoelectric components, which leads to energy savings, has led to the formation of multilayered structures [21][22][23][24][25][26][27][28] since electrode cost becomes an issue, as in the case of multilayer ceramic capacitors. 20) The authors have reported on reduction-resistant BaTiO 3 -based piezoelectric materials with excellent electrical properties.…”
Section: Introductionmentioning
confidence: 99%